Gesondheid: 'n realistiese perspektief - Elna Gross; Anna Nolte; Dawie Smith (AOSIS, 1996)
This article presents a realistic perspective on the definition of health. Debates in tins article include amongst others the World Health Organization's definition on health and the'7 Nursing for the Whole Person " health definition." Opsomming Die term gesondheid was nog altyd moeilik om te definieer, omdat daar soveel uiteenlopende beskouiings is oor wat die begrip gesondheid behels. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.